Suspected diphtheria turn out to be Bacillus cereus: A rare case study (Indian Journal of Case Reports, 2026)
Bacillus cereus rarely causes respiratory tract infections. We present a suspected case of diphtheria with sepsis, which turned out to be B. cereus. A 6-year-old female child presented with fever, cough, dyspnea, and dysphagia. On examination, bilateral submandibular swelling and pseudomembrane were present in the oral cavity. A throat swab and blood were taken for microbiological examination. Gram stain of throat swab showed Gram-positive bacilli, and there were no Corynebacterium diptheriae-like bacilli in Albert’s stain. B. cereus grew both in the throat swab and the blood. Antibiotics were changed according to the culture report. Targeted therapy was successful, and the patient was discharged uneventfully. This is a rare case highlighting B. cereus as a potential pathogenic cause for a life-threatening infection in otherwise immunocompetent children whose vaccination status was complete. Microbiological testing, such as stains and culture, is essential for accurate diagnosis and timely management.